Edukasi Pola Asuh Pemberian Makanan Pendamping ASI (MP-ASI) pada bayi dan Balita di Desa Alue Sentang Kec. Birem Bayeun Kab. Aceh Timur - Maya Sari; Elvina Sari; Hanafi Nasution (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Nutrition is an indicator of the successful growth and development of babies and toddlers. Thus, nutritional needs must be met to achieve this success. Fulfillment of nutrition begins when the baby is in the womb, then exclusive breastfeeding for the first 6 months of life and continued with complementary breastfeeding (MP-ASI). The aim of providing MP-ASI is to maintain the nutritional status of infants and toddlers. By providing proper MP-ASI, the growth and development of babies and toddlers will be optimal. Mothers have an important role in preparing and serving the right MP-ASI for their babies. In particular, the mother's knowledge has a big influence on the mindset and caring attitude towards the success of providing appropriate MP-ASI. (Cindy, 2023) The aim of this community service activity is to increase mothers' knowledge about providing complementary breast milk (MP-ASI) in Alue Sentang Village, Kec. Birem Bayeun District. East Aceh. The method used in this activity is the Participatory Action Research (PAR) approach, which is an approach to learning in solving problems and meeting the practical needs of society, as well as the production of knowledge. The results obtained from this activity are an increase in mothers' knowledge about giving complementary foods to breast milk. so that it is hoped that the knowledge gained can be realized in everyday life.